Comparative evaluation of fracture resistance and mode of failure of ceramic veneers with different design preparations - Nitin Sharma; Rajeev Gupta; Archana Nagpal; Vishal Katna; Rupandeep Kaur Samra (Wolters Kluwer Medknow Publications, 2021)
Background: Ceramic veneers is one of the conservative esthetic treatment modality in dentistry. Success of veneer is very much dependent on the design preparation. Materials and Methods: Thirty selected teeth were categorized within three groups of 10 each with varying design preparations. After mounting the specimens, the incisal reduction was done, and porcelain laminate veneers were fabricated. Then cementation of the veneers was done with resin-cement, and fracture load was applied and recorded. Results: Multiple comparisons were done using post-hoc Tukey's test and modality of failure of veneers among the different designs were done using Chi-square test with the level of significance fixed at 0.05. Conclusion: Ceramic veneers preparation design including1 mm incisal reduction along with 1 mm of palatal-chamfer height revealed greater fracture toughness in contrast to incisal-reduction 1 mm along with butt-joint preparation design.